Introducing HyPeak: An international network on hydropeaking research, practice, and policy. (30th May 2022) - Alp, Maria; Batalla, Ramon J.; Bejarano, Maria Dolores; Boavida, Isabel; Capra, Hervé; Carolli, Mauro; Casas‐Mulet, Roser; Costa, Maria João; Halleraker, Jo Halvard; Hauer, Christoph; Hayes, Daniel S.; Harby, Atle; et al.
Abstract: An increase in the demand for renewable energy is driving hydropower development and its integration with variable renewable energy sources. When hydropower is produced flexibly from hydropower plants, it causes rapid and frequent artificial flow fluctuations in rivers, a phenomenon known as hydropeaking. Hydropeaking and associated hydrological alterations cause multiple impacts on riverine habitats with cascading effects on ecosystem functioning and structure. Given the significance of its ecological and socio‐economic implications, mitigation of hydropeaking requires an inter‐ and transdisciplinary approach. An interdisciplinary network called HyPeak has been conceived to enrich international research initiatives and support hydropower planning and policy. HyPeak has been founded based on exchange and networking activities linking scientists from several countries where hydropeaking has been widespread for decades and numerous studies dedicated to the topic have been carried out. HyPeak aims to integrate members from other countries and continents in which hydropower production plays a relevant role, and grow to be a reference group that provides expert advice on the topic to policy‐makers, as well as researchers, stakeholders, and practitioners in the field of hydropeaking.